Citrulline as a Biomarker in the Murine Total-Body Irradiation Model. Issue 5 (November 2015) - Jones, Jace W.; Tudor, Gregory; Li, Fei; Tong, Yan; Katz, Barry; Farese, Ann M.; MacVittie, Thomas J.; Booth, Catherine; Kane, Maureen A.
<x xml:space="preserve">Abstract</x> Abstract The use of plasma citrulline as a biomarker for gastrointestinal acute radiation syndrome via exposure to total-body irradiation in a murine model was investigated. The radiation exposure covered lethal, mid-lethal, and sub-lethal gastrointestinal acute radiation syndrome. Plasma citrulline profiles were generated over the first 6 d following total-body irradiation exposure of 6–15 Gy. In addition, plasma citrulline was comprehensively evaluated in the context of matching small intestine citrulline and histopathology. Higher plasma citrulline was significantly associated with lower irradiation doses over the first 6 d following the irradiation insult. Furthermore, higher plasma citrulline was significantly associated with higher crypt survival. The correlation of the plasma citrulline to crypt survival was more robust for higher irradiation doses and for later time points. The data suggested plasma citrulline was most informative for reflecting gastrointestinal injury resulting from exposure to 9–15 Gy total-body irradiation covering time-points 2–5 d post the irradiation insult.